Raising awareness about worms for students at the public school in the city of Formiga-MG - Borges, Douglas Lopes; Corrêa, Hellen de Almeida; Arantes, Héllen Rascilam; Campos, Lorrainy Caroliny; Rosa, Nubia Garcia; Ribeiro, Lília Rosário (Seven Editora, 2023)
Introduction: Parasitic diseases, including helminth infections, are among the neglected tropical diseases and represent a serious public health issue in emerging countries such as Brazil. Several factors such as lack of basic sanitation, poor hygiene conditions, and lack of awareness about the subject can be the cause of the problem. Objectives: The purpose of this project was to carry out an extension action aimed at raising awareness about parasitic diseases, specifically targeting students in the lower secondary education level. Methodology: Due to the prevalence of parasitic infections among school-age children, the extension project on the theme of "parasitic diseases" was developed in a primary school in the municipality of Formiga, Minas Gerais. The project involved students from the 6th to 9th grades. The activity was carried out in two stages: in the first stage, Biomedicine students from UNIFOR gave an informative lecture using audiovisual resources about the main parasitic infections in the region. In the second stage, preserved specimens of worms and videos showing live parasites were presented. Results: The elementary school students remained attentive and curious throughout the entire presentation, and at the same time, they were also somewhat apprehensive when they had the opportunity to see the parasites beyond the screens. This experience provided them with valuable knowledge that they can share with their friends and family, especially regarding the prevention of intestinal parasitic infections. Conclusion: This project provided all participants with relevant scientific knowledge about parasitic infections, creating a network for spreading awareness about the subject to more people. In this way, the extension activity contributed to the development of more conscious and informed citizens regarding the topic at hand, potentially assisting in the reduction of local cases of parasitic infections. For the supervising undergraduate students, the activity offered scientific deepening about parasitic infections, as well as a greater understanding of the socioeconomic and sanitary issues that affect the community at large. DOI:https://doi.org/10.56238/alookdevelopv1-121